Explosive eighteen : a Stephanie Plum novel - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2012)
Before Stephanie can even step foot off Flight 127 Hawaii to Newark, she is knee deep in trouble. Her dream vacation turned into a nightmare, and she is flying back to New Jersey solo. Worse still, her seatmate never returned to the plane after the L.A. layover. Now he is dead, in a garbage can, waiting for curbside pickup. And a ragtag collection of thugs and psychos, not to mention the FBI, are all looking for a photograph the dead man was supposed to be carrying. Only one other person has seen the missing photo, Stephanie Plum. Now she is the target, and she does not intend to end up in a garbage can.